2010
DOI: 10.1016/j.visres.2010.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the integration of spatial frequency-based information in natural scenes

Abstract: It is known that visual information is processed separately and based on multiple spatial frequencies. Therefore, integration of information is important for categorization of natural scenes. To clarify the time course of visual integration, we examined categorization accuracies for spatially filtered images as a function of image exposure duration. Results indicated that, with image durations of 100-ms, accuracy was superior with spatially integrable images when compared with accuracy levels based upon the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…The time courses of frequency and phase processing have both previously been studied independently, using different stimuli and tasks (Kihara & Takeda, 2010;Rousselet et al, 2008). Evidence from those studies suggested that phase spectrum information is available for visual tasks with a delay of approximately 40 ms after amplitude spectrum information becomes available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The time courses of frequency and phase processing have both previously been studied independently, using different stimuli and tasks (Kihara & Takeda, 2010;Rousselet et al, 2008). Evidence from those studies suggested that phase spectrum information is available for visual tasks with a delay of approximately 40 ms after amplitude spectrum information becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…Kihara and Takeda (2010) investigated the time course of this process in an experiment that used a natural image categorization task. They found an advantage for composite low-and high-pass filtered stimuli over probability summation of separate filtered images between 83 and 100 ms after stimulus onset, implying that integration of channel outputs has begun by this time.…”
Section: Combined Effects Of Manipulating Phase and Amplitude Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the 83 categorization of LSF-only objects outperformed the categorization of HSF objects for the 84 exposure durations of up to 250 ms, suggesting a prior for LSF information in early 85 processing in this kind of categorization task (Kihara & Takeda, 2010). The differences did 86 not change when attentional demands were increased, suggesting that the effects are based on 87 the first feedforward processing (Kihara & Takeda, 2012).…”
mentioning
confidence: 90%
“…Spatial frequency information at different scales contributes to object categorization from around 100 ms of exposure duration (Kihara & Takeda, 2010, 2012. Importantly, the 83 categorization of LSF-only objects outperformed the categorization of HSF objects for the 84 exposure durations of up to 250 ms, suggesting a prior for LSF information in early 85 processing in this kind of categorization task (Kihara & Takeda, 2010).…”
mentioning
confidence: 99%